Actor Phenomena: Case Study of Illegal Gold Mining in the Suso Watershed (Das Suso), Luwu Regency - Yusril Hidayat; Gustiana Kambo; Muhammad (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
This writing investigates the involvement of local actors or powerful people in Indonesia regarding the exploitation of illegal gold mines in the Suso watershed, Luwu district. The involvement of actors in responding to government policies in closing the illegal mines. The results of this research on the involvement of actors show that these actors are seen as local strongmen due to illegal mining activities in the Suso watershed. What is the actor’s role that appears and can control the mining activity. The ways in which actors intervene in government policies in closing illegal mining activities. These actors succeeded in building strengths by exploiting the weaknesses of the Country in this case, namely building networks with parties involved in formal and non-formal institutions. The actor's success in building variant power, and succeeding in controlling illegal miners who carry out activities in the gold mine in the Suso watershed, Luwu Regency. Actors manage to control policies. Manipulations carried out by actors to seek profit from illegal mining activities.